Carbon fractions in soil under no-tillage corn and cover crops in the Brazilian Cerrado - Ramos, Maria Lucrécia Gerosa; Silva, Vivian Galdino da; Carvalho, Arminda Moreira de; Malaquias, Juaci Vitoria; Oliveira, Alexsandra Duarte de; Sousa, Thais Rodrigues de; Silva, Stefany Braz (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate soil carbon fractions under cover crops cultivated after corn (Zea mays), with or without nitrogen topdressing fertilization, in a long-term experiment in the Brazilian Cerrado. The experiment was carried out in a randomized complete block design, in split-plots with three replicates. The plots were represented by the cover crops, and the subplots, by the presence or absence of N topdressing for corn. The following cover crop species were planted after the harvest of the 30F53VYHR corn hybrid: 'BRS Mandarin' pigeonpea (Cajanus cajan), sunn hemp (Crotalaria juncea), oilseed radish (Raphanus sativus), and black mucuna (Mucuna aterrima). After the cutting of the cover crops, soil samples were collected at 0.0‒0.10 and 0.10‒0.20 m soil depths. After corn harvest, samples of its residues were taken. The cover crops alter the soil chemical and physical fractions, especially fulvic acid and soil particulate organic carbon. Nitrogen topdressing for corn decreases fulvic acid, but increases the humic acid/fulvic acid ratio and particulate organic carbon in the deeper soil layer.